Physico-mechanical properties and potential utilization of melia azedarach L. grown in Quezon Province, the Philippines - Marasigan, Oliver S. (Philippine Journal of Science, 2024)
The possible utilization of Bagalunga (Melia azedarach L.) was determined based on its physical and mechanical properties. Tests were done following the ASTM D143-2019 standard. Tree samples were collected from two municipalities of Quezon province, the Philippines – namely Sariaya and Unisan. The results showed that compared to the trees from Sariaya, the trees collected from Unisan had 13.48 and 14.24% higher green moisture content (MC) and basic relative density (RD), respectively. However, their tangential (TS), radial (RS), longitudinal (LS), and volumetric shrinkage (VS) were 12.21, 4.42, 28.94, and 7.83% lower than those of the former. Furthermore, the RD of M. azedarach was similar to that of Gmelina arborea, and Acacia mangium and higher than that of Falcataria falcata. As for VS, it was comparable and in some cases even higher than those of commercially used timber species with medium to low VS. For the strength properties, in both green and 12% MC conditions, the strength of trees from Unisan was significantly higher than trees from Sariaya. However, both remained within the medium strength classification – similar to Swietenia macrophylla, G. arborea, and A. mangium but higher than Eucalyptus deglupta, Hevea brasiliensis, and F. falcata. The significant effect of axial height was observed in MC, RD, LS, and VS, and minimal variation was found in the mechanical properties. Industrial tree plantation developers may consider using M. azedarach as an alternative species, with careful consideration of the axial height and location, as these factors can influence tree properties.